Serum MIC-1, LMTK-3 and IGFBP-7 levels in the prognosis of lung cancer treated with ablation combined with chemotherapy: Serum MIC-1, LMTK-3 and IGFBP-7 levels in lung cancer - Fu, Yilin; Shi, Lifeng; Lu, Quanxin; Yu, Fatao; Hong, Xiaofeng; Zeng, Guoliang; Li, Meng (Journal of Medical Biochemistry, 2025)
Objective To explore the value of the serum levels of macrophage inhibitory factor 1 (MIC-1), Lemur tyrosine kinase 3 (LMTK-3), and insulin-like growth factor binding protein 7 (IGFBP-7) in the prognosis assessment of patients with advanced lung cancer treated with ablation combined with chemotherapy. Methods 190 patients with advanced lung cancer who received care at this hospital between January 2022 and June 2024 were chosen to be part of the lung cancer group. The healthy control group consisted of 90 healthy people who attended the hospital and had physical tests over the same time period. Percutaneous microwave thermal ablation treatment was used to treat every patient with advanced lung cancer, and chemotherapy was administered within one week after treatment. The levels of serum MIC-1, LMTK-3 and IGFBP-7 before and after treatment and before treatment in patients with different therapeutic effects in the lung cancer group and the healthy control group were compared. Univariate and multivariate analyses were conducted on the factors affecting the prognosis of patients to analyze the efficacy of serum MIC-1, LMTK-3 and IGFBP-7 levels in predicting the prognosis of patients with advanced lung cancer. Results Serum MIC-1 and LMTK-3 levels in the lung cancer group were substantially higher than those in the healthy control group both before and after therapy (P<0.05). Serum MIC-1 and LMTK-3 levels in the lung cancer group were much lower after therapy than they were before, and the difference was statistically significant (P<0.05). The serum IGFBP-7 level in the lung cancer group before and after treatment was significantly lower than that in the healthy control group (P<0.05). After treatment, the serum IGFBP-7 level in the lung cancer group was significantly greater than that before treatment (P<0.05). Patients with lung cancer experienced 29 cases of stable response (SD)+ progressive response (PD) and 66 cases of complete response (CR)+ partial response (PR) following treatment. Those with SD+PD advanced lung cancer had significantly higher blood MIC-1 and LMTK-3 levels prior to treatment than those with CR+PR advanced lung cancer. The serum IGFBP-7 level of advanced lung cancer patients with SD+PD before treatment was significantly lower than that of advanced lung cancer patients with CR+PR. In patients with advanced lung cancer, elevated blood MIC-1 and LMTK-3 levels and lower IGFBP-7 levels prior to treatment were independent risk factors for death within a year following treatment (P<0.05). The combined detection of the serum MIC-1, LMTK-3 and IGFBP-7 levels for the prediction of death within one year after treatment for advanced lung cancer had a sensitivity of 91.3%, a specificity of 95.8%, and an AUC of 0.974. Its AUC was significantly greater than that of MIC-1 (Z=2.378, P=0.017) and LMTK-3 (Z=2.897). The AUC was detected separately for IGFBP-7 (Z=3.213, P=0.001), however, the AUC for each of the three indicators did not differ statistically significantly (P>0.05).. Conclusion Important markers for assessing the effectiveness of chemotherapy and ablation in the treatment of advanced lung cancer are serum MIC-1, LMTK-3, and IGFBP-7. With the help of combination detection, the prognosis of patients with advanced lung cancer after therapy can be predicted.